2002
DOI: 10.1021/jf0117199
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidative Functions of Natto, A Kind of Fermented Soybeans:  Effect on LDL Oxidation and Lipid Metabolism in Cholesterol-Fed Rats

Abstract: Natto water-soluble fractions, low-molecular-weight viscous substance, and soybean water extract, which had an inhibitory effect on the oxidation of low-density lipoproteins (LDL) in vitro, were fed to rats for 3 weeks. These fractions had no influence on the growth of rats, which were fed a basal diet containing 1% cholesterol, but lowered plasma triglyceride and total cholesterol. Inhibition of copper-oxidation of plasma and LDL ex vivo, and a reduction in lipid peroxidation in liver and aorta in vivo, were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
40
0
1

Year Published

2004
2004
2017
2017

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 103 publications
(49 citation statements)
references
References 28 publications
2
40
0
1
Order By: Relevance
“…Given the results, it was confirmed that the intake of CS diet would be superior lowering TG than that of TC diet. This result was similar to the reduced effect of TG by soy protein intake reported to the existing (Iwai et al, 2002;Liao et al, 2007). Especially, according to Liao et al, it determined that protein ingredient in soybean had an effect on the serum TG reduction (Liao et al, 2007).…”
Section: )supporting
confidence: 90%
See 1 more Smart Citation
“…Given the results, it was confirmed that the intake of CS diet would be superior lowering TG than that of TC diet. This result was similar to the reduced effect of TG by soy protein intake reported to the existing (Iwai et al, 2002;Liao et al, 2007). Especially, according to Liao et al, it determined that protein ingredient in soybean had an effect on the serum TG reduction (Liao et al, 2007).…”
Section: )supporting
confidence: 90%
“…For example, the obesity by the increase of TG concentration and the circulatory disease (Arteriosclerosis and Table 5 Effects of experimental diets on serum TG/PL, T-C/PL or T-C/HDL-C and LDL-C/HDL-C ratios in rats See footnote Table 1 2) a-f: Means with the same letter superscript in histograms are not significantly different at the 5% level by Duncan's multiple range test heart disease etc.) by increase of T-C and LDL-C can be given (Ando et al, 1998;Iwai et al, 2002). However, the rats fed on Cheonggukjang increased HDL-C and decreased for LDL-C, TG, and T-C.…”
Section: )mentioning
confidence: 99%
“…22) This indicates that molecules other than isoflavones might have synergistic effects on the in vivo antioxidant enzyme induction of tofu. Moreover, aqueous extracts of natto and tempeh also have strong antioxidant potential in vivo, 23,24) while soybean protein inhibits lipid peroxidation in the plasma. 25) Our results indicate that peptides and amino acids were liberated during douchi fermentation, and that the antioxidant activity of the douchi depended on the increase in peptides with fermentation, rather than on the increase in isoflavone aglycons.…”
Section: )mentioning
confidence: 99%
“…Recent surveys have demonstrated that isoflavones in soybeans act as antioxidants (11,12), improve lipoprotein profiles (13), delay osteoporosis in the elderly (14,23) and may protect against cancer (15). These effects are independent of vitamin K action as a cofactor of ␥-glutamyl carboxylase.…”
Section: Discussionmentioning
confidence: 99%